Pengaruh Pintu Keluar Mall Bumi Kedaton dan U Turn Sebelum Lintas Jalan Rel di Jalan Sulta Agung (Studi Kasus Simpang Jl. Teuku Umar – Jl. ZA. Pagar Alam – Jl. Sultan Agung) - Nadi, M. Abi Berkah; Herianto, Dwi; Sebayang, Syukur (Universitas Lampung, 2015)
This research used primary data and secondary data. The primary data is obtained from the directsurvey result in the form of geometry data, environmental condition data, traffic flow, signaltiming, and long queues. Secondary data consists of the population in Bandar Lampungat 2012that is get from BPS Lampung Province. Data analysis is used the Indonesian Manual HighwayCapacity in 1997 for Signalized Intersections. Based on calculations, it can found that theintersection level of service at aftrenoon peak hour was F with a delay amount 61,50sec/pcu, levelof service at evening peak hour was F with a delay amount 88, 20sec/pcu, and level of service atnight peak hour was F with a delay amount 60, 29sec/pcu. Similarly, with the U Turn result canobtained the intersection level of service at afternoon peak hour was B, level of service at eveningpeak hour was B, and level of service at night peak hour was A.It indicates that the performance ofintersectionis not optimal. To increase the performance of the intersection, need make a changesin the pattern of setting time control become the pattern of not setting time control based on thepeak condition by changing the cycle time, green time, and inter green time. And therecommendation needed for the handling of openings U Turn on Jl. Sultan Agung.Keywords : signalized intersection, delay, performance, U Turn